Gamification in Online Learning: A Systematic Review of Engagement and Learning Outcomes in Digital Education - Guntur Arie Wibowo; Saliman Saliman (Online Learning In Educational Research (OLER), 2025)
The education sector has seen substantial changes in the last 10 years due to digital transformation, particularly with the adoption of online learning models. Despite the flexibility it offers, maintaining student engagement and achieving the best possible learning outcomes remain the biggest challenges. The purpose of this research is to investigate how gamification, as a novel approach to improving student motivation and engagement, affects learning outcomes in an online learning environment. A Systematic Literature Review (SLR) was employed, which involved gathering and examining 49 peer-reviewed scientific publications from many top databases. To detect trends and important conclusions, data were evaluated utilizing mixed methodologies, qualitative, and quantitative approaches. The findings of the study demonstrate that gamification components like leaderboards, badges, and points greatly improve learning outcomes and student engagement, however their efficacy varies depending on how and where they are used. In addition to providing useful advice for teachers looking to create more dynamic and captivating learning environments, this study significantly advances the notion of gamification in online education